The claustrum of the bottlenose dolphin Tursiops truncatus (Montagu 1821) - Cozzi, Bruno; Roncon, Giulia; Granato, Alberto; Giurisato, Maristella; Castagna, Maura; Peruffo, Antonella; Panin, Mattia; Ballarin, Cristina; Montelli, Stefano; Pirone, Andrea (Frontiers in Systems Neuroscience, 2014)
The mammalian claustrum is involved in processing sensory information from the environment. The claustrum is reciprocally connected to the visual cortex and these projections, at least in carnivores, display a clear retinotopic distribution. The visual cortex of dolphins occupies a position strikingly different from that of land mammals. Whether the reshaping of the functional areas of the cortex of cetaceans involves also modifications of the claustral projections remains hitherto unanswered. The present topographic and immunohistochemical study is based on the brains of 8 bottlenose dolphins and a wide array of antisera against: calcium-binding proteins (CBPs) parvalbumin (PV), calretinin (CR), and calbindin (CB); somatostatin (SOM); neuropeptide Y (NPY); and the potential claustral marker Gng2. Our observations confirmed the general topography of the mammalian claustrum also in the bottlenose dolphin, although a) the reduction of the piriform lobe modifies the ventral relationships of the claustrum with the cortex, and b) the rotation of the telencephalon along the transverse axis, accompanied by the reduction of the antero-posterior length of the brain, apparently moves the claustrum more rostrally. We observed a strong presence of CR-immunoreactive (-ir) neurons and fibers, a diffuse but weak expression of CB-ir elements and virtually no PV immunostaining. This latter finding agrees with studies that report that PV-ir elements are rare in the visual cortex of the same species. NPY- and somatostatin-containing neurons were evident, while the potential claustral markers Gng2 was not identified in the sections, but no explanation for its absence is currently available. Although no data are available on the projections to and from the claustrum in cetaceans, our results suggest that its neurochemical organization is compatible with the presence of noteworthy cortical inputs and outputs and a persistent role in the general processing of the relative information.